Analysis of surface recombination in nanowire array solar cells - Yu, Shuqing; Roemer, Friedhard; Witzigmann, Bernd (Journal of Photonics for Energy, 2012)
In this work, microscopic three-dimensional simulations were performed on nanowire array solar cells to study the impact of surface recombination (SR) on the photovoltaic performance. Both axially and radially arranged p-n junction in III-V-based structures were taken into consideration. From the cases with SR velocity varying from 1e3 cm/s to 1e6 cm/s, the radial p-n-junction nanowire was found to provide better tolerance for SR. The SR difference within the axial and radial p-n-junction structures is explained by analyzing the relevant minority carrier density, followed by a discussion on the impact of SR on the diffusive nature of minority carriers. © 2012 Society of Photo-Optical Instrumentation Engineers (SPIE).
CRIS-Team Scopus Importer:2021-06-11
Keywords: Carrier transport properties; Nanowire; Photovoltaics; Semiconductor; Solar cell